The Effect of Breast Self-Examination Program on Self-Examination Skills and Self-Examination Behavior in Female Students Bansomdejchaopraya Rajabhat University - chaiwcharn, Tamaporn; Prasansri, Alongkot; Hachawi, Chidchai (Vajira Nursing Journal, 2024)
This research is quasi-experimental research. (Quasi-experimental research) to study and compare breast self-examination skills and behavior before and after participating in the program of the experimental group and the control group. and to study to compare breast self-examination skills and behavior before and after participating in the program between the experimental group and the control group. The research tools included 1) breast self-examination program. that the researcher created by applying protection motivation theory (Rogers) 2) general information questionnaire 3) breast self-examination skills assessment form 4) breast self-examination behavior questionnaire. The sample group is divided into the experimental group of 35 people and the control group of 35 people. The experimental group received a breast self-examination program that applied protection motivation theory (Rogers). The control group received normal instructions. Data collection 12 weeks, and data were analyzed using descriptive statistics, paired sample t-test, and independent t-test. The study results were as follows the experiment, the experimental group had average scores on breast self-examination skills and behaviors. Statistically significantly higher than before the experiment (p<0.001) After the experiment, the experimental and control groups had average scores on breast self-examination skills. The difference is not statistically significant. After the experiment, the experimental group had a significantly higher mean score for breast self-examination behavior than the control group (p<0.001). The results of this study show that the breast self-examination program resulted in the sample having better breast self-examination skills and better breast self-examination behavior.